Psychometric Evaluation of the Dutch Version of the Assessment of Preschool Children's Participation (APCP): Construct Validity and Test–Retest Reliability. (1st November 2013) - Bult, Maureen K.; Verschuren, Olaf; Kertoy, Marilyn K.; Lindeman, Eline; Jongmans, Marian J.; Ketelaar, Marjolijn
ABSTRACT The aim of this study is to examine construct validity, internal consistency, and test–retest reliability of the Dutch translation of the Assessment of Preschool Children's Participation (APCP) a participation measure for children aged 2 to 5 years and 11 months with and without physical disabilities. Parents of 126 preschool children participated. Sixty-seven of the children had no physical disabilities (mean age three years two months, SD 1.2) and 59 children had physical disabilities (mean age two years nine months, SD 1.8). Validity was tested using three hypotheses regarding having a physical disability, gender and age differences. Most, but not all hypotheses were confirmed. Children with a physical disability participated in fewer activities and with lower intensity than children without physical disabilities (p < .001). Boys and girls participated in an equally wide variety of activities and with similar intensity except for skill development. Four- to five-year-old children in general participated in more activities than two- to three-year-old children and had a higher intensity score (p < .001). For activity types, age differences were found for skill development (p < .001) and social activities (p < .001). Internal consistency was sufficient for four out of 10 activity types. Intra Class Correlations for test–retest reliability ranged from 63 to .91. Our findings indicate that the Dutch APCP shows sufficient psychometric properties for some but not all aspects of the measure.